Analysis Of The Effect Of E-Wom Involvement On Consumer Buying Intention On Oppo Products On The Youtuber Gadgetin Channel - Gayuh Dwi Prakoso; Rahab Rahab; Nosirzoda Sheroz (Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
This research was carried out with the purpose of analyzing the involvement of e-WOM on the purchase intention of Oppo products on the YouTube channel Gadgetin. e-WOM involvement is influenced by factors such as information quality, information credibility, website quality, innovativeness, social support, and attitudes toward e-WOM. The research sample consists of of 200 participants who have watched videos on the Gadgetin channel on YouTube and the Partial Least Square (PLS) analysis technique is performed. According to the findings of this study, the factors of information credibility, website quality, innovativeness, social support, and attitudes towards e-WOM all have an influence on e-WOM involvement and e-WOM involvement has an influence on purchase intention. The research also found that innovativeness has an influence on e-WOM involvement. On the other hand, the variable of information quality did not have any effect on the involvement of e-WOM in this study. Managerial implications and suggestions for future study is provided in the article based on the result.